Influence of N-2/H-2 and N-2 plasma on binary III-nitride films prepared by hollow-cathode plasma-assisted atomic layer deposition - ALEVLİ, MUSTAFA (A V S AMER INST PHYSICS, 2018)
The authors reported the hollow-cathode plasma-assisted atomic layer deposition of AlN, GaN, and InN films using N-2-only and N-2/H-2 plasma. In this study, the authors analyzed the effect of plasma gas composition on the properties of deposited binary III-nitride thin films. Toward this goal, AlN, GaN, and InN films were deposited on Si (100) substrates using N-2-only (50 sccm), as well as N-2/H-2 (50+50, 50+25 sccm) plasma to investigate the impact of H-2 flow. Grazingincidence x-ray diffraction (GIXRD) patterns of AlN and GaN thin films deposited with N-2/H-2 plasma remained almost unchanged when H-2 flow decreased from 50 to 25 sccm. On the other hand, the use of N-2 plasma without any H-2 resulted in amorphous GaN thin films with significant carbon impurity within the bulk film. In the case of AlN, similar behavior was observed as the crystal structure is significantly altered to amorphouslike material. Thicknesses of AlN and GaN thin films increased tremendously when N-2-only was used as the plasma gas. Furthermore, refractive index values of both AlN and GaN films decreased upon the use of N-2-only plasma, which confirm the deterioration of the film quality. Structural weaknesses of GaN and AlN films deposited with N-2-only plasma are due to presences of carbon impurities that are trapped inside the growing film. Interestingly, the authors did not observe similar results in InN films grown with N-2/H-2 plasma. For InN, GIXRD and spectroscopic ellipsometry results show that the phases of deposited films change from InN to In+InN as H-2 content in the plasma gas is increased. On the other hand, InN films grown with N-2-only plasma show improved structural properties. However, significantly higher N-2 plasma exposure times are needed to minimize the residual carbon content in deposited InN layers. Published by the AVS.
Keywords: THIN-FILMS; DEFORMATION POTENTIALS; OPTICAL-CONSTANTS; INN; ALN; GAN; ELLIPSOMETRY; TEMPERATURES; E-1(TO); GROWTH